2014
DOI: 10.1007/s00167-014-2961-1
|View full text |Cite
|
Sign up to set email alerts
|

Failures in bipolar fresh osteochondral allograft for the treatment of end-stage knee osteoarthritis

Abstract: Purpose Bipolar fresh osteochondral allografts (BFOA) recently became a fascinating option for articular cartilage replacement, in particular in those young patients nonsuitable for traditional replacement because of age. While the use of osteochondral allografts for the treatment of focal osteochondral lesions in the knee is well established, their use in the treatment of end-stage arthritis is far more controversial. The purpose of this paper is to describe our experience in a series of seven patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
0
35
0
1
Order By: Relevance
“…Relative contraindications for OCA include end-stage osteoarthritis and very restricted range of motion 30. 0.00 92.86 Relative contraindications for ACI include end-stage osteoarthritis and very restricted range of motion.…”
mentioning
confidence: 99%
“…Relative contraindications for OCA include end-stage osteoarthritis and very restricted range of motion 30. 0.00 92.86 Relative contraindications for ACI include end-stage osteoarthritis and very restricted range of motion.…”
mentioning
confidence: 99%
“…Dieser Zielkonflikt ist nicht einfach zu lösen (Kontakt vs. Schichtdicke; [49]). Hier können individuell mechanisch einstellbare Sägelehren [19] oder individuell digital geplante und geprintete Schnittblöcke (. Abb.…”
Section: Multiplanare Und Multipolare Flocsatunclassified
“…PTKO is most frequently detected on the elderly population, with an estimated 15 million cases in China (2). Survey data in the United States also demonstrated that PTKO is the second most common cause of disability in males >50 years old, after cardiovascular disease (3). Thus, prevention and treatment of PTKO have become one of the most difficult issues in clinical practice at present (3).…”
Section: Introductionmentioning
confidence: 99%